Efficient cultivation of Kluyveromyces Lactis in high cell density culture in fed-batch cultivation system - Mohd Shafiq, Mohd Sueb (2012)
Kluyveromyces lactis is beneficial and well-known yeast due to its status of GRAS that has made the yeast as a vital microorganism for the subject of studies and also the applications of industry such as a possible source of single-cell protein with expected probiotic properties, oligonuci eotide-derived flavour enhancers and lactic acid. In addition,High Cell Density Cultivation (HCDC) of K. lactis has been scientifically and biotechnologically important trend in improving microbial mass and product formation substantially.More importantly,fed-batch strategy has been identified as another effective mean to increase the yield by preventing substrate limitation or inhibition through maintaining medium substrate concentration at a low level during cultivation.In this study,there were two system cultivations have been employed which was batch cultivation and fed-batch cultivation. Further studies have been done under batch cultivation on the aeration effect and dissolved The results showed that 1.0 v/v/inin aeration rate gave relatively high cell dry weight, CDW, 18.6 gIL. On the contrary, the results from DO stat value of 60% showed substantial increment with CDW of 28.7 gIL.As for the fed-batch study, constant feeding rate strategy has been applied with two different feeding substrates i.e complete media and mono-lactate. The CDW harvested for complete media had showed remarkable result, 59.75 g/L as compared to CDW produced from lactose as a sole feeding substrate, 44.75 g/L.02,DO.